ON THE DETERRENT EFFECT OF INDIVIDUAL VERSUS COLLECTIVE LIABILITY IN CRIMINAL ORGANIZATIONS - HAURET, Laetitia; LANGLAIS, Eric; SONNTAG, Carine (Journal of Advanced Research in Law and Economics; Vol 2 No 4 (2011): JARLE, Volume II, Issue 2(4), Winter 2011, 2017)
Our paper addresses the question of the deterrent effect of a monetary sanction associated to a collective rather than an individual liability, when crimes are realized within a hierarchical gang (defined as a criminal organization where the leader is a sleeping partner and several agents are active partners in the illegal or criminal activity). We develop a model where the active gang members face contradictory incentives to commit a crime. On the one hand, public authorities try to deter each gang member by imposing sanctions; on the second, the leader of the gang try to keep his members enough active in the gang by threatening them of private sanctions. We show that sanctions based on individual liability are inefficient to deter gang’s members since the leader overreacts on the public sanctions. In contrast, we show that a regime of collective liability, allowing the judge to sanction the sleeping partner even if he hasn’t realized any crime himself, can reach enough deterrence of the members of the gang.